2011
DOI: 10.3310/hta15070
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of bacterial DNA testing for central venous catheter-associated bloodstream infection in children with cancer

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 138 publications
(232 reference statements)
0
4
0
Order By: Relevance
“…The technique can be performed with normally sterile biological specimens and also on artificial devices (5-10). However, current studies based on molecular detection of catheter-related bloodstream infection mainly measure levels of bacterial DNA in blood samples drawn through the catheter using commercially available real-time PCR (17)(18)(19). Therefore, at present, no data are available on the yield of universal 16S rRNA PCR performed on the catheter in situ, irrespective of the type of catheter.…”
Section: Discussionmentioning
confidence: 99%
“…The technique can be performed with normally sterile biological specimens and also on artificial devices (5-10). However, current studies based on molecular detection of catheter-related bloodstream infection mainly measure levels of bacterial DNA in blood samples drawn through the catheter using commercially available real-time PCR (17)(18)(19). Therefore, at present, no data are available on the yield of universal 16S rRNA PCR performed on the catheter in situ, irrespective of the type of catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that neonatal sepsis is often associated with lower colony forming units of bacteria in the blood [25,26], which may contribute to the low biomass of the extracted microbial DNA. A previous study demonstrated that the microbial DNA load of blood (> 0.5 pg/μl) collected from the catheters (n = 207) in children with cancer can detect catheter infections in 61% (95% CI 44 to 83%) of those classified as probable central venous catheter-associated infection with 88% specificity (95% CI 84 to 92%) [27]. High DNA load was associated with higher specificity for diagnosing catheter infection and predicted subsequent catheter removal in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial therapy should be stopped in case that the cause of sepsis was detected as something other than infection. The removal of infected intravascular devices, especially central venous catheters, if possible and if preferred to antibiotic lock methods, will reduce mortality and increase the chances that the infection will be cured [5,64].…”
Section: Antimicrobial Therapymentioning
confidence: 99%